A masquerader: A report of rapid progressive primary intraocular lymphoma - Mat Abu, Siti Hajar; Hashim, Hanizasurana; Aziz, Roslin Azni; Ngah, Norfariza; Hussein, Adil; Othman, Noriah (Elsevier, 2013)
Primary intraocular lymphoma (PIOL) is an uncommon subset of primary central nervous system lymphoma (PCNSL). We report a rapid progressive of this disease in a 73 years old lady who presented with one year history of left eye floaters, associated with deterioration of left vision. Examination revealed left eye vitritis and typical vitreous clumps. Left vitrectomy and vitreous biopsy was performed with result showed few singly dispersed atypical lymphoid cells. She was diagnosed to have Primary Intraocular lymphoma and was started on intravitreal methotrexate. Initially she responded well but later the tumour spread to liver, breast and brain within a year. She finally succumbed to the disease. High index of suspicion of PIOL is mandatory in all elderly patients presenting with panuveitis. Co-management with the Neurologist is vital in the continuous management of these patients in view of the high rate of mortality.